2021
DOI: 10.1002/sim.9278
|View full text |Cite
|
Sign up to set email alerts
|

A puzzle of proportions: Two popular Bayesian tests can yield dramatically different conclusions

Abstract: Testing the equality of two proportions is a common procedure in science, especially in medicine and public health. In these domains, it is crucial to be able to quantify evidence for the absence of a treatment effect. Bayesian hypothesis testing by means of the Bayes factor provides one avenue to do so, requiring the specification of prior distributions for parameters. The most popular analysis approach views the comparison of proportions from a contingency table perspective, assigning prior distributions dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…It is important to recognise that the post‐test probabilities can be calculated using pre‐test probabilities other than 0.5 (see Appendix 1 in reference [9]). Furthermore, several approaches may be used to calculate a Bayes factor for the equivalence of two proportions, including analytic methods [12, 21], as used here, and by simulated statistical testing [11, 13]. Different methods yield different values for the Bayes factor, although in our experience not dramatically so.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to recognise that the post‐test probabilities can be calculated using pre‐test probabilities other than 0.5 (see Appendix 1 in reference [9]). Furthermore, several approaches may be used to calculate a Bayes factor for the equivalence of two proportions, including analytic methods [12, 21], as used here, and by simulated statistical testing [11, 13]. Different methods yield different values for the Bayes factor, although in our experience not dramatically so.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the bias against the null hypothesis is 0.1182. On the other hand, the bias in favor of the null hypothesis is measured by computing (5) with θ 0 = 0.1 ± 0.05, which gives 0.0504 (for θ 0 = 0.15) and 0.0204 (for θ 0 = 0.05). This shows an acceptable bias either for or against the null hypothesis for the uniform [0, 1] prior.…”
Section: Example 1 (Clinical Trial; [24])mentioning
confidence: 99%
“…Furthermore, ref. [5] provided some recommendations for using Bayes factors in testing the equality of two proportions to improve the sensitivity of the test. Several studies can also be found in the literature on developing the Bayesian two-sample proportion test in contingency tables for testing the independence between rows and columns.…”
Section: Introductionmentioning
confidence: 99%
“…The two approaches make different assumptions, ask different questions, and therefore provide different answers (cf. Dablander et al, 2022).…”
Section: Bayesian Statisticsmentioning
confidence: 99%
“…This article is a tutorial, and consequently we will emphasize the assumptions, interpretations, and practical application of the test. A more advanced discussion of the software can be found in Gronau et al (2021), and an associated statistical paradox is presented in Dablander, Huth, Gronau, Etz, and Wagenmakers (2022).…”
mentioning
confidence: 99%